New Strategies to Enhance Myocardial Regeneration: Expectations and Challenges from Preclinical Evidence - Rurali, Erica; Vinci, Maria C.; Bassetti, Beatrice; Barbagallo, Veronica; Pompilio, Giulio; Gambini, Elisa (Current Stem Cell Research & Therapy, 2020)
Nowadays, cardiac regeneration is an emerging topic in the cardiovascular field because of the compelling need for effective therapies for repairing or replacing cardiac tissue damaged by pathological or physiological conditions. Indeed, irreversible myocardial remodeling which follows acute myocardial infarction represents a serious burden of this century. In this context, a great improvement in pharmacological and interventional techniques is accompanied by a big challenge of cardiac regenerative medicine. In the last 20 years, several clinical trials tried to investigate the role of different types of stem cells in promoting cardiac repair. However, the promising results obtained in the preclinical trials have not yet been reproduced in patients. Thus, the development of novel strategies to improve stem cell efficiency became imperative. Here, an overview of the more recent cell types proposed for cardiac regeneration is presented, together with the most interesting approaches to enhance cell regenerative potential as well as cell-free approaches.
Keywords: Myocardial infarction